2021
DOI: 10.1098/rspb.2020.2793
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell immune repertoire and transcriptome sequencing reveals that clonally expanded and transcriptionally distinct lymphocytes populate the aged central nervous system in mice

Abstract: Neuroinflammation plays a crucial role during ageing and various neurological conditions, including Alzheimer's disease, multiple sclerosis and infection. Technical limitations, however, have prevented an integrative analysis of how lymphocyte immune receptor repertoires and their accompanying transcriptional states change with age in the central nervous system. Here, we leveraged single-cell sequencing to simultaneously profile B cell receptor and T cell receptor repertoires and accompanying gene expression p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
3
21
2
Order By: Relevance
“…Surprisingly, we observed minor transcriptional differences between these two populations of cells when performing unsupervised clustering and differential gene expression analysis. Transcriptional differences were however observed in IgM-, IgA-and IgG-expressing B cells, which was consistent with previous results (Neumeier et al, 2021a), as well as expansion-specific transcriptional clustering (Kuhn et al, 2021;Yermanos et al, 2021a).…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, we observed minor transcriptional differences between these two populations of cells when performing unsupervised clustering and differential gene expression analysis. Transcriptional differences were however observed in IgM-, IgA-and IgG-expressing B cells, which was consistent with previous results (Neumeier et al, 2021a), as well as expansion-specific transcriptional clustering (Kuhn et al, 2021;Yermanos et al, 2021a).…”
Section: Discussionsupporting
confidence: 92%
“…We lastly questioned whether including repertoires lacking specificity to GP33 could provide contrast for how similar the 6 repertoires were following acute, chronic, and latent infection. Including publicly available data from either naive PBMCs (10x genomics) or CNS-resident T cells (Yermanos, Neumeier, et al 2021) demonstrated clear separation between the repertoires of GP33-specific T cells and naive T cells (Figure 4C), further supporting the notion that the GP33-specific repertoire has stereotypic germline gene usage irrespective of the infection condition.…”
Section: Stereotypic Germline Gene Usage Following Acute Chronic and Latent Viral Infectionmentioning
confidence: 56%
“…We next integrated TCR sequence with transcriptomes at single-cell resolution. It has been previously demonstrated that highly expanded clones upregulate effector molecules such as Nkg7 , Ccl5 , and granzymes (Yermanos, Agrafiotis, et al 2021; Yermanos, Neumeier, et al 2021). Therefore, we first focused our analysis on the 30 most expanded clones for each infection by quantifying the fraction of cells present in each transcriptional cluster (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of singlecell sequencing (scSeq) has revolutionized the resolution at which clonal selection of immune repertoires can be quantified (Friedensohn et al, 2017). For example, scSeq workflows have been established that enable the simultaneous recovery of both full-length, paired BCR or TCR sequence (VDJ), and full transcriptome [gene expression (GEX)] information, thereby providing a crucial link between clonal selection and expansion with a high-dimensional transcriptional cell phenotype (Horns et al, 2020;Khatun et al, 2021;Yermanos, Neumeier, et al, 2021;Mathew et al, 2021;Lindeman et al, 2018;Stubbington et al, 2016). Interpreting such datasets, however, remains challenging as the accompanying computational pipelines and software are still in their infancy (Yermanos, Agrafiotis, et al, 2021b;Borcherding et al, 2020;Sturm et al, 2020).…”
Section: Introductionmentioning
confidence: 99%